Sunglass tint does not impact the indoor catching performance of cricket fielders - Christie, C. J.; Nellemann, S.; Davies, T.; Fourie, J. L.; Davy, Jonathan Patrick (Frontiers in Sports and Active Living, 2023)
Introduction Sunglasses are worn by outdoor athletes such as cricketers for many reasons, including comfort and glare reduction, which may help to improve vision. Anecdotally they are purported to have performance-enhancing benefits, but there is a lack of evidence for this. Further, it appears that fielders are the only position in cricket who wear sunglasses. Therefore, this study aimed to compare the catching performance of fielders when wearing three different colour sunglasses tints during an indoor, laboratory-based experiment. Methods Twenty-one male cricketers currently playing for a university or amateur provincial teams in Makhanda, South Africa, who were non-habitual sunglass wearers, were recruited for this study. An optometrist administered pre-screening tests. Players had four testing sessions during which they wore a different colour tint at each session indoors (clear, blue, G30 (rose), and red). Players were required to catch 18 balls projected from a bowling machine. The number of balls caught, as well as the quality of the catch, was recorded. At the final session, they were asked which tint they thought was best. Results Pre-screening tests showed that the red lens was best for contrast sensitivity and stereopsis. During data collection, sunglass tint did not affect catching performance. The players perceived the red lens as the worst and the G30 as the best. Discussion It can be concluded that catching performance indoors is not affected by tint colour.